The Commonification of Food as an Approach for the Achievement of Food Security: and the Realisation of the Right to Food for All - Wasonga Orago, Nicholas (Strathmore Law Journal, 2020)
The commodification of food is one of the many causes of food insecurity as it occasions the inability of poor households to access the available food because of high prices and dysfunctional markets. A change of approach from commodification to commonification to deal with food insecurity at the national, regional and global level is the way to go. As commodification of food is a social construct adopted as a result of deliberate societal policy-making, commonification can similarly be adopted through legal and institutional design at the local, national and international levels; creating polycentric systems for the management of food-producing resources for the local communities. With commonification, decisions relating to the use of local resources for the production, processing, distribution and consumption of food are made at the local level, to ensure that other socioeconomic and cultural aspects of food are considered in the decision-making processes. The integrated aspects of the right to food and food democracy are critical components of the commonification approach to food security.